'The world as we know it' – revisiting the rock art at Bergbukten 4B in Alta, northern Norway. (3rd July 2019) - Gjerde, Jan Magne
ABSTRACT: The Alta rock art area in northern Norway has more than 6000 carvings made between about 5200–1BC. The focus for this paper is the Bergbukten 4B panel in Alta. With more than 200 figures this is one of the largest panels with Stone Age rock art in northern Europe. The panel holds several scenes, compositions and narratives. Studying relations between the figures and the interaction with the natural features of the rock canvas show some of the rock art refers to activities and places of activities mirroring real places. Moreover, the figures are also placed in relation to a three-tiered cosmological framework. This intertwined 'world as we know it' can be interpreted as a cosmographical knowledge of the hunter-fisher-gatherers making the rock art in the Stone Age about 6000–7000 years ago where real and imaginary landscapes were part of a cosmographical representation visualizing their 'memoryscapes' stored in the rocks.